Antibodies against a β-glucan-protein complex of Candida albicans and its potential as indicator of protective immunity in candidemic patients - Antonella Torosantucci (Nature Portfolio, 2017)
Abstract Sera from candidemic and non-candidemic subjects were examined for antibodies against the cell wall β1,3- and β1,6-glucans, as well as the β-glucan-associated protein MP65 of Candida species. Although antibodies against each of the above components were detected in all subjects, candidemic patients had lower antibody titers against β1,3-glucan, but higher antibody titers against β1,6-glucan and MP65, than non-candidemic subjects. The elevated levels of anti-β1,6-glucan and -MP65 antibodies found in candidemic patients were independent on the patient risk category, APACHE II score, presence of co-morbidities, β1,3-glucanemia level, Candida isolate, and antifungal treatment. Interestingly, however, the anti-MP65, but not the anti-β1,6-glucan antibodies, of candidemic patients had higher titers in survivors than in non-survivors, particularly in those subject categories with the highest mortality (>65-years old, diabetic, or septic shock patients). Thus, candidemic patients are capable of boosting anti-Candida immune responses upon infection, and some of these responses might be associated to the generation of protective immunity in patients with candidemia.